2021
DOI: 10.1002/jev2.12139
|View full text |Cite
|
Sign up to set email alerts
|

An engineered CD81‐based combinatorial library for selecting recombinant binders to cell surface proteins: Laminin binding CD81 enhances cellular uptake of extracellular vesicles

Abstract: The research of extracellular vesicles (EVs) has boomed in the last decade, with the promise of them functioning as target‐directed drug delivery vehicles, able to modulate proliferation, migration, differentiation, and other properties of the recipient cell that are vital for health of the host organism. To enhance the ability of their targeted delivery, we employed an intrinsically overrepresented protein, CD81, to serve for recognition of the desired target antigen. Yeast libraries displaying mutant variant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Several studies have reported tetraspanins as valuable tools for engineering and tracing cellsecreted EVs with fluorescent markers (Suetsugu, 2013) , (Yoshimura et al, 2016) , (Mathieu et al, 2021). Specifically, CD81 was fused with fluorescent reporters (Stickney et al, 2016) , (Zuppone et al, 2023) or used as a direct targeting moiety against human placental laminin (Vogt et al, 2021). In this work, CD81 fusion proteins were exploited to track the cell engagement of secreted, heterologous EV sub-populations.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported tetraspanins as valuable tools for engineering and tracing cellsecreted EVs with fluorescent markers (Suetsugu, 2013) , (Yoshimura et al, 2016) , (Mathieu et al, 2021). Specifically, CD81 was fused with fluorescent reporters (Stickney et al, 2016) , (Zuppone et al, 2023) or used as a direct targeting moiety against human placental laminin (Vogt et al, 2021). In this work, CD81 fusion proteins were exploited to track the cell engagement of secreted, heterologous EV sub-populations.…”
Section: Discussionmentioning
confidence: 99%
“…Laminins are major signaling and structural molecules of basement membranes and modulate several diverse cellular functions. These include maintaining tissue structure, adhesion and migration, differentiation and survival [ 66 , 67 ]. In oral squamous cell carcinoma (OSCC) LN1-1 cell-derived EVs, laminin-332 proteins were validated as highly expressed proteins, including laminin α3, β3 and γ2 [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…4A). Common transmembrane proteins include the lysosomeassociated membrane protein 2B (LAMP-2B) [124], tetraspanins [29,125,126], glycosyl-phosphatidyl-inositol (GPI) [127], C1C2 [128], and platelet-derived growth factor receptors (PDGFR) [31,129], among others (Fig. 4A).…”
Section: Indirect Modificationmentioning
confidence: 99%
“…As a viable and straightforward strategy, the tetraspanin superfamily (CD63/CD9/CD81) is often selected for EV modification with target molecules [29,125,136]. By conjugating CD63 with apoprotein-A1 and further bonding to scavenger receptors expressed on hepatocellular carcinoma cells, engineered EVs showed a twofold increase in uptake for targeted delivery [136].…”
Section: Indirect Modificationmentioning
confidence: 99%